A tanulás tanulásának vizsgálata általános iskolások körében - Habók, Anita (Magyar Pedagógia, 2011)
Research on learning to learn has been in the focus of attention in recent decades. It has drawn increased attention since it was placed among the key competencies. This paper provides an overview of the theoretical background on learning to learn. It presents the most important approaches connected to this term, namely the narrow and broad versions. The study then provides an overview of the content, implementation and assessment of related projects. After considering international experience, we commenced the development of measurement instruments. This research was part of the Developing Diagnostic Assessments project at the University of Szeged. One aim of the study was to develop a questionnaire which is suitable to describe schoolchildren’s characteristics in the area of learning to learn and which provides data for further developmental work. The questionnaire contains the following main fields: learning motivation and strategies, self-concept and self-esteem, learning environment, perceived support from significant other, and learning relationships. Participants were randomly selected schoolchildren in years 3 and 6 in Hungary. Results showed significant higher means in the main fields for year 3 children as compared to those in year 6, except for learning relationships. In this case, in the subfield of critical thinking, no significant differences were observed between the two groups. We found the highest positive correlations between subfields of the questionnaire. Results and experience are to be used for the development of further measurement instruments. The next step regarding learning to learn is to investigate the cognitive field.